Development model of rock relief on thick horizontal and gently sloping rock strata exposed to rain - Knez, Martin; Slabe, Tadej; Drame, Leon (Acta Carsologica, 2021)
Due to various factors influencing diverse rocks, karst phenomena take unique shapes that are most often reflected in the rock relief. Through a series of different developmental factors, new factors first gradually transform the traces of old formations and over time, if they are distinct enough, they can replace them with completely new ones. In places old forms are reflected in the formation of a new rock relief only indirectly. The rock relief of karst phenomena, in this case karren, also develops under the influence of a single factor. Developmentally, rock forms, due to dissection of the surface and lasting of development, often in several layers merge into one another. A development model enables us to discover the overall development of the formation of the selected part of the rocky karst surface. The individual rock forms which have merged into the rock relief represent just one stage of development. Good knowledge of the overall development enables us to discern the development so far and predict future development. A number of development models can be discerned. One of the basic models reveals the manner of the rain-induced formation and development of horizontal and gently sloping carbonate rock strata into karren and stone forests, especially after the disintegration of the upper (thinner) rock strata and the denudation and shaping of the bottom strata. It reveals many characteristics of rock formation, from the sheet flow to the formation of rain flutes, their merging into rain channels and the development of funnel-like notches; that is, developmental transition of rock forms and rock relief in the overall development from the flat surface to its dissection into peaks.